Physical activity and sedentary behavior in relation to mortality among renal cell cancer survivors. - Daniela Schmid; Charles E Matthews; Michael F Leitzmann (PLoS ONE, 2018)
Background The relations of physical activity and sedentary behavior to mortality risk among patients with renal cell cancer have not yet been evaluated. Methods We conducted a prospective cohort study among 667 renal cell cancer survivors aged 50-71 years of the National Institutes of Health (NIH)-AARP Diet and Health Study with a median follow-up time of 7.1 years. Post-diagnosis physical activity, TV viewing, and total sitting time were assessed using self-administered questionnaires. Hazard ratios (HRs) and 95% confidence intervals (CIs) for mortality were estimated using Cox proportional hazards models. Results Increasing levels of moderate to vigorous physical activity were related to decreased risk of overall mortality [multivariable-adjusted HRs for <1 hr/wk (reference), 1 to 3 hrs/wk, ≥3 to <7 hrs/wk, and ≥7 hrs/wk = 1.0, 1.16, 0.94, and 0.60 (95% CI = 0.38-0.96; p-trend = 0.03)]. In contrast, television viewing was associated with increased risk of overall mortality in the age- and sex-adjusted model (HR for >4 hrs/d vs. 0 to 2 hrs/d = 1.52, 95% CI = 1.02-2.26; p-trend = 0.04), but the relation was attenuated following further control for other covariates (multivariable-adjusted HR = 1.44, 95% CI = 0.92-2.24; p-trend = 0.11). Total sitting time was unrelated to all-cause mortality. Conclusion Among renal cancer patients, moderate to vigorous physical activity is associated with decreased risk of overall mortality. Clinicians should consider discussing the potential benefits of physical activity for longevity among survivors of renal cell cancer.